Child mental health and income gradient from early childhood to adolescence: evidence from the UK - Yang, M; Carson, C; Creswell, C; Violato, M (Elsevier, 2023)
Background Children from low income families are likely to have poorer mental health than their more affluent peers. However, it is unclear how this association varies at different developmental stages and what the potential underpinning mechanisms are. This study investigates the relationship between family income and mental health problems from early childhood to adolescence in the UK, and examines the potential mediating role of family-related factors over time.